Metastatic breast cancer during pregnancy: a case report - Widi, Made Yudha Ganesa Wikantyas; Putra, Wayan Artana; Kusuma, Anak Agung Ngurah Jaya; Wiradnyana, Anak Agung Putra; Sanjaya, I Nyoman Hariyasa; Budiana, I Nyoman Gede; Mahayasa, Putu Doster; Marta, Kadek Fajar (Indonesian Journal of Perinatology, 2025)
Introduction: Breast cancer is the most prevalent malignancy among women and a notable comorbidity during pregnancy. Pregnancy-associated breast cancer (PABC) presents unique challenges due to physiological breast changes that complicate early diagnosis. This case report aimed to present a 31-year-old female with a diagnosis of bilateral breast tumors, pleural effusion, and multiple thoracic soft tissue tumors during her second pregnancy, highlighting the complexities and treatment considerations involved. Case presentation: A 31-year-old female patient, referred to Prof. Dr. I. G.N.G Ngoerah General Hospital, Denpasar, was in her second pregnancy at 20-21 weeks of gestation. She presented with bilateral breast lumps, worsening pain, and shortness of breath. Her obstetric history included a previous cesarean delivery and two abortions. Clinical examination revealed pleural effusion and multiple nodules suggestive of metastases. Biopsies confirmed tubular adenoma in the right breast and invasive breast carcinoma in the left breast. Ultrasound and chest x-ray findings indicated metastases to the liver and lungs. The patient was diagnosed with G4P1021 at 20 weeks of gestation with pregnancy-associated bilateral breast cancer and metastases. Conclusion: PABC diagnosis and treatment are fraught with challenges due to the need to balance maternal and fetal health. Delays in diagnosis, limited antenatal care, and the aggressive nature of PABC contribute to poor outcomes. This case underscores the necessity of early detection, prompt multidisciplinary intervention, and tailored treatment strategies to improve PABC patients' prognoses.